Is Epstein-Barr Virus Infection Associated With Thyroid Tumorigenesis?—A Southern China Cohort Study - Yu, Shi-Tong; Ge, Jun-Na; Li, Rui-Chen; Wei, Zhi-Gang; Sun, Bai-Hui; Jiang, Yu-Ming; Luo, Jing-Yi; Liu, Hao; Lei, Shang-Tong (Frontiers in Oncology, 2019)
Abstract Background: Epstein-Barr virus (EBV) is associated with many epithelial malignancies. A few reports on the association between EBV and thyroid tumorigenesis have been investigated. However, the conclusion is highly contradictory. We aimed to explore the role EBV played in thyroid nodules development and its clinical significance in a cohort from southern China. Method: We conducted a retrospective data abstraction study of patients who underwent thyroidectomy between December 2017 and June 2018. We retrospective analyzed the clinicopathological parameters and EBV infection status (serological antibodies and in situ hybridization). Result: The cohort comprised 384 patients newly diagnosed thyroid diseases, including 261 papillary thyroid carcinomas, 87 nodular goiters, 21 follicular adenomas, 12 follicular thyroid carcinomas, and 3 medullary thyroid carcinomas. There were 42 (10.9%) patients identified as serological antibodies positive. However, there was no association between clinicopathological parameters and serological antibodies positive. And, none of patients were identified EBER expression in thyroid normal/cancer cell nucleus in the in situ hybridization. Conclusion: This study, no correlation between EBV and thyroid tumorigenesis was found in a southern China cohort.